2001
DOI: 10.1007/bf02234296
|View full text |Cite
|
Sign up to set email alerts
|

Defining a learning curve for laparoscopic colorectal resections

Abstract: The learning curve for performing colorectal resections was approximately 30 procedures in this study, based on a decline in operating time, intraoperative complications, and conversion rate. Learning was also extended to clinical care because it was appreciated that patients could be discharged to their homes more quickly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
234
1
19

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(273 citation statements)
references
References 12 publications
11
234
1
19
Order By: Relevance
“…This is probably because of the initial technical difficulties in advanced laparoscopic skills in bowel mobilisation and resection given the fact that laparoscopic surgery is still evolving in India. This procedure has a definitive learning curve [7,8] and it is said that it takes 30 number of surgeries to plateau the curve. We feel that a good experience in open colorectal surgeries is a prerequisite to master laparoscopic colorectal surgery.…”
Section: Resultsmentioning
confidence: 99%
“…This is probably because of the initial technical difficulties in advanced laparoscopic skills in bowel mobilisation and resection given the fact that laparoscopic surgery is still evolving in India. This procedure has a definitive learning curve [7,8] and it is said that it takes 30 number of surgeries to plateau the curve. We feel that a good experience in open colorectal surgeries is a prerequisite to master laparoscopic colorectal surgery.…”
Section: Resultsmentioning
confidence: 99%
“…However, 52 patients in our series had a postoperative diagnosis of a pT4 cancer (9 pT4b), reflecting that CT scan sensitivity for the preoperative diagnosis of T4 colorectal cancer is suboptimal [27]. Some studies have investigated the learning curve in LCR [3,14,[28][29][30][31][32][33], observing the trend in operative time and conversion rate according to the surgeon's experience. For instance, Marusch et al [29] showed a significantly lower conversion rate for surgeons with experience of more than 100 LCRs than for surgeons who had performed fewer than 100 such procedures.…”
Section: Discussionmentioning
confidence: 99%
“…A curva de aprendizado é longa, sendo muitas vezes necessária a utilização de simuladores e cirurgias em animais, além de experiência em cirurgias por doenças benignas, antes da realização cirurgias para tratamento de tumores 18,20,24,25 .…”
Section: Introductionunclassified